Electron time-of-flight measurements in sulfur interpreted via an extra surface mobility channel - Mergulh, S.; Ferreira, G. F. Leal; Moreno, R. A.; Figueiredo, M. T. de (American Physical Society (APS), 1988)
Time-of-flight measurements were carried out in orthorhombic sulfur for various fields, ranging from -2 to -20 kV/cm. No dependence of the mobility with the electric field was found but the current, normalized by the initial current, showed an electric field dependence at small times, decaying faster for larger electric field. After the failure of the usual models in explaining the resultsincluding the assumption of depth-dependent density of trapsa model assuming an extra mobility channel near the surface provided a reasonable set of parameters independent of the electric field. The measurements were carried out at 8.5, 29, 53, 68, and 79°C. © 1988 The American Physical Society.